Análise causal intertemporal do consumo de combustíveis fósseis na emissão de dióxido de carbono nos países do G7 - Martins, Tailon (2021)
Since the Industrial Revolution, the world has relied on non-renewable energy sources and the participation of fossil fossils, throughout history, has been fundamental to strengthening the economy of many countries. Despite leveraging economic growth, there has been an intense increase in carbon dioxide emissions into the atmosphere. Although there may still be uncertainties about the magnitude of the impacts of this gas, global warming is one of the main consequences, causing concerns from the perspective of economic and sustainable development. Therefore, this research arises with the objective of determining the intertemporal relationship in the short and long term dynamics caused by the consumption of coal, oil and natural gas in the emission of carbon dioxide by the G7 countries in the period from 1965 to 2018. To achieve the proposed objective, the Auto-regressive and Distributed Lag and Bound test models for detecting cointegration were used. As a result, due to structural breaks in the variables, the best model selected was the one that incorporated two dummy variables for the break periods (1978 and 1990). Positive unidirectional causality was identified, in the sense that the consumption of fossil fuels provides an increase in carbon dioxide emissions. Short-term elasticities indicate that an increase of 1 percentage point in the consumption of oil, coal and natural gas will cause, respectively, an increase of 0.4823%, 0.3140% and 0.1717% in carbon dioxide emissions. In the long run, the increase of 1 percentage point in the consumption of oil, coal and natural gas will cause, respectively, an increase of 0.4924%, 0.2692% and 0.1829% in carbon dioxide emissions. The error correction model indicates that 47.39% of a shock in the carbon dioxide emissions variable is resolved in one year, such that, after 2 years, the carbon dioxide emissions return to long-term equilibrium.